Connectivity-based segmentation of the periaqueductal gray matter in human with brainstem optimized diffusion MRI. - Ezra, M; Faull, O; Jbabdi, S; Pattinson, K (Wiley, 2014)
The periaqueductal gray matter (PAG) is a midbrain structure, involved in key homeostatic neurobiological functions, such as pain modulation and cardiorespiratory control. Animal research has identified four subdivisional columns that differ in both connectivity and function. Until now these findings have not been replicated in humans. This study used high-resolution brainstem optimized diffusion magnetic resonance imaging and probabilistic tractography to segment the human PAG into four subdivisions, based on voxel connectivity profiles. We identified four distinct subdivisions demonstrating high spatial concordance with the columns of the animal model. The resolution of these subdivisions for individual subjects permitted detailed examination of their structural connectivity without the requirement of an a priori starting location. Interestingly patterns of forebrain connectivity appear to be different to those found in nonhuman studies, whereas midbrain and hindbrain connectivity appears to be maintained. Although there are similarities in the columnar structure of the PAG subdivisions between humans and nonhuman animals, there appears to be different patterns of cortical connectivity. This suggests that the functional organization of the PAG may be different between species, and as a consequence, functional studies in nonhumans may not be directly translatable to humans. This highlights the need for focused functional studies in humans.